Milk yield and composition of crossbred Sahelian × Anglo-Nubian goats in the semi-intensive system in Mali during the preweaning period - Sanogo, Souleymane; Shaker, Mohamed Momani; Nantoumé, Hamidou; Salem, Abdel-Fattah Z M (Tropical animal health and production, 2013)
The aim of this study was to evaluate milk yield and its composition during the preweaning period for Sahelian goats (SG) and Anglo-Nubian (AN) crossbred depending on some factors. The experiments were conducted from January to December 2008 for 44 suckled and hand-milked does, randomized, and divided into two equal groups: SG (n = 22) and F(1) Anglo-Nubian × Sahelian goats (1/2AN; n = 22). The does and their offsprings were kept in a pen where they stayed indoors for 45 days before they were allowed outdoors when the weather was suitable. Each category received supplemental feeds depending on the season (rainy season, dry cold season, and dry hot season). The average daily milk yield was recorded weekly from parturition to 100 days of age. Individual milk samples were taken for chemical analysis in connection with the yield measurements twice per month from the fourth week of lactation throughout the different seasons (rainy, cold dry, and hot dry). The daily milk yield differed between breed types (P = 0.001) during the preweaning, while the effect of kids' sex on daily milk production was not significant. Litter size affected milk yield up to day 60 (P = 0.032) where does with twins producing more milk than those with single kid. However, at day 100, both groups had similar (P = 0.001) milk production. Total milk yield at weaning increased by 103 % in 1/2AN over SG. The highest concentration of total solids of milk was (12.76 %) recorded in the hot dry season. The results of this study indicate that crossbreeding native Sahelian goats with high potential Anglo-Nubian buck improved milk production and its composition.
Keywords: lineární modely; Sex Factors; Breeding; druhová specificita; Crosses, Genetic; Dairying; kozy; Female; odstavení; chov; Mali; zvířata; křížení genetické; sexuální faktory; roční období; mlékárenství; ženské pohlaví; Milk; Goats; Linear Models; Seasons; Species Specificity; Animals; mléko; Weaning